2020
DOI: 10.1021/acssensors.9b01941
|View full text |Cite
|
Sign up to set email alerts
|

Booster, a Red-Shifted Genetically Encoded Förster Resonance Energy Transfer (FRET) Biosensor Compatible with Cyan Fluorescent Protein/Yellow Fluorescent Protein-Based FRET Biosensors and Blue Light-Responsive Optogenetic Tools

Abstract: Genetically encoded Forster resonance energy transfer (FRET)based biosensors have been developed for the visualization of signaling molecule activities. Currently, most of them are comprised of cyan and yellow fluorescent proteins (CFP and YFP), precluding the use of multiple FRET biosensors within a single cell. Moreover, the FRET biosensors based on CFP and YFP are incompatible with the optogenetic tools that operate at blue light. To overcome these problems, here, we have developed FRET biosensors with red-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 73 publications
(131 reference statements)
0
34
0
Order By: Relevance
“…Once caspase-3 is activated, it cleaves the linker in O-DEVD-FR, resulting in the separation of mKOκ and mKate2, and the consequent reduction in FRET signal in apoptotic cells ( Figure 1B ). It was recently demonstrated that mKOκ-mKate2 FRET pair is compatible with CFP-YFP FRET pair because they use different spectral windows ( Watabe et al, 2020 ). Thus, it is possible to use both biosensors to fluorescently image ATP level and caspase-3 activity in the same apoptotic cell ( Figure 1C,D ).…”
Section: Resultsmentioning
confidence: 99%
“…Once caspase-3 is activated, it cleaves the linker in O-DEVD-FR, resulting in the separation of mKOκ and mKate2, and the consequent reduction in FRET signal in apoptotic cells ( Figure 1B ). It was recently demonstrated that mKOκ-mKate2 FRET pair is compatible with CFP-YFP FRET pair because they use different spectral windows ( Watabe et al, 2020 ). Thus, it is possible to use both biosensors to fluorescently image ATP level and caspase-3 activity in the same apoptotic cell ( Figure 1C,D ).…”
Section: Resultsmentioning
confidence: 99%
“…Our engineering strategies that optimized the relative placement and the relative orientation of the fluorescent protein pair on the sensor can expand the search space for any FRET-based sensor using green and red fluorescent proteins. These approaches could improve the dynamic range of FRET-based sensors of potassium ions and protein kinase activity that also employ green-red fluorescent protein pairs 33 , 35 , 52 , 54 , 55 . New sensors that employ our fluorescent protein configuration will take advantage of the green-red fluorescent FRET pairs’ inherent advantages compared to cyan-yellow-fluorescent FRET pairs; these sensors would thus enable imaging experiments with low phototoxicity, high FRET efficiency response, and deep tissue penetration in live animal preparations 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strong fluorescence from Müller cells in the IPL and GCL of the hyBRET‐AMPK and GO‐ATeam2 retinas (Figures 1 and S4) will enable a comparison of the AMPK activity and ATP level between Müller glial cells and low‐fluorescence neurons. The applications can be expanded by combining this approach with the cell type‐specific expression of the FRET biosensor 34 and simultaneous multicolor measurements with a red‐shifted sensor variant 35 . However, a major technical limitation of the two‐photon excitation microscopy is the concomitant activation of the phototransduction cascade 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The applications can be expanded by combining this approach with the cell type-specific expression of the FRET biosensor 34 and simultaneous multicolor measurements with a red-shifted sensor variant. 35 However, a major technical limitation of the two-photon excitation microscopy is the concomitant activation of the phototransduction cascade. 36 The estimated rhodopsin activation is 1 × 10 3 R* rod −1 scan −1 under our typical imaging condition.…”
Section: Discussionmentioning
confidence: 99%